International Justice Court Between Acceptance Of Its Jurisdiction And The Binding Of Its Decisions - يسرى غريب (Latakia University Journal - Economic and Legal Sciences Series, 2024)
The International Court of Justice, in accordance with the Charter of the United Nations, constitutes the primary judicial arm of the United Nations, and upon undertaking its judicial and advisory function, it is responsible for contributing with the rest of the branches of the United Nations to achieving the purposes of this organization in establishing international peace and security. For this purpose, the Court is competent to decide international disputes between states according to two methods: Either optionally, when the parties to the conflict explicitly agree on its jurisdiction, or compulsory, if the parties previously agreed on its jurisdiction in accordance with international agreements or individual statements. The decisions of the International Court of Justice has binding force and has the authority of the matter adjudicated. It is obligatory to implement it by the parties to the conflict, and in the event of refraining from doing so, the Security Council can be resorted to for implementation according to certain mechanisms. As for the advisory opinion, it does not have any mandatory value and does not have the force of a res judicata, but it has great moral and legal value.